Analisis Aksiologis terhadap Potensi Pemanfaatan Blue Carbon pada Sedimentasi Mangrove di Pulau Lombok - Nanda Fitria Wardani; Muhammad Sarjan (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The potential of blue carbon in mangrove ecosystem sedimentation has become an important approach to mitigating global climate change. Mangrove ecosystems have a high capacity to absorb and store carbon, particularly in sediments that are stable over long periods. This study aims to analyze the potential of blue carbon and its utilization from an axiological perspective on Lombok Island. The method employed is a qualitative descriptive-analytical approach based on a literature study, using an axiological framework that includes ecological, economic, social, and ethical values. The results indicate that mangrove sediments are the primary component in carbon storage, contributing dominantly to the total carbon stock. The utilization of blue carbon is developing through economic schemes such as carbon trading and payments for ecosystem services, reflecting a transformation from ecological functions into economic instruments. However, this utilization has the potential to create value tensions among economic, ecological, and social aspects. Therefore, an axiological approach is necessary to ensure that the utilization of blue carbon remains aligned with the principles of sustainability and environmental justice, particularly in the context of mangrove management on Lombok Island.